2011
DOI: 10.1177/1354068810382935
|View full text |Cite
|
Sign up to set email alerts
|

Who selects the party leader?

Abstract: We study the degree of formal influence that rank-and-file members have on the selection of party leaders in the five English-speaking Westminster countries: Australia, Canada, Ireland, New Zealand and the United Kingdom. We find that in recent years there has been a general, though not universal, trend towards granting party members greater influence in the choice of their leader. We observe that the decision to broaden the selectorate has been made by most parties in the UK, Canada and Ireland, while parties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 46 publications
1
95
0
3
Order By: Relevance
“…I argue that this evolution reflects a shift in democratic norms according to which parties' successes are judged as well as arguments in the electoral competition. Indeed most of these reforms have started in parties that had found themselves in opposition, before spreading through to competitors (W. Cross and Blais, 2012). Reformers 'recognised the political salience of the nature of participation opportunities within parties and used perceived popular pressure to justify rule changes that expand the set of intra-party decisionmakers' (Scarrow and Kittlilson, 2003, p. 75).…”
Section: Democracy and Participation As Incentivesmentioning
confidence: 99%
“…I argue that this evolution reflects a shift in democratic norms according to which parties' successes are judged as well as arguments in the electoral competition. Indeed most of these reforms have started in parties that had found themselves in opposition, before spreading through to competitors (W. Cross and Blais, 2012). Reformers 'recognised the political salience of the nature of participation opportunities within parties and used perceived popular pressure to justify rule changes that expand the set of intra-party decisionmakers' (Scarrow and Kittlilson, 2003, p. 75).…”
Section: Democracy and Participation As Incentivesmentioning
confidence: 99%
“…They have argued that political parties continue to pursue linkage because their electoral stability (Poguntke 2002;Scarrow 2009), legitimacy (Warner 2000, p. 164;Allern 2010) and even-to a certain extent-funding (Pedersen et al 2004), continue to depend on it. Their research has shown that parties have tended to encourage the active involvement of members (and in some cases sympathisers) by strengthening their rights in candidate and leadership selection (Caul Kittilson & Scarrow 2003;Hazan & Rahat 2010;Cross & Blais 2012) and party policy-making (Gauja 2009). It has also demonstrated that parties have maintained formal ties (Aarts 1995;Poguntke 2002) and, most importantly, enhanced their informal interactions with civil society groups through joint committee meetings, common campaigns and invitations to civil society organisations, whose purpose is to engage them in drawing up party manifestos and key decision-making (Thomas 2001;Poguntke 2006;Allern 2010).…”
mentioning
confidence: 99%
“…Cross and Blais (2012) contend, therefore, that Westminster party elites only reluctantly transfer more power from the parliamentary party group to party members.The party elites only do so when they are forced to and/or when finding themselves in a weak position: after an electoral defeat, when in opposition, when other parties are adopting direct member votes or when the party is new.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of party primaries is in Cross and Blais' (2012) view a zero-sum game: more power to one (group of) party actor(s) means less power for another (group of) party actor(s). In parties operating as a 'cartel party' (Katz and Mair, 1995), party elites have become professionalised and operate often autonomously from the basis of the party in order to respond to the wishes of the electorate.Therefore, party elites only reluctantly grant more involvement to (organised) party members and only do so when they are forced to and/or when finding themselves in a weak position.…”
mentioning
confidence: 99%